Crotalus Durissus Ruruima: Current Knowledge on Natural History, Medical Importance, and Clinical Toxinology - Pucca, Manuela B.; Bernarde, Paulo Sérgio; Rocha, Anderson Maciel; Viana, Patrik F.; Farias, Raimundo Erasmo Souza; Cerni, Felipe A.; Oliveira, Isadora S.; Ferreira, Isabela G.; Sandri, Eliseu A.; Sachett, Jacqueline; Wen, Fan Hui; Sampaio, Vanderson; et al. (Frontiers in Immunology, 2021)
Crotalus durissus ruruima is a rattlesnake subspecies mainly found in Roraima, the northernmost state of Brazil. Envenomings caused by this subspecies lead to severe clinical manifestations (e.g. respiratory muscle paralysis, rhabdomyolysis, and acute renal failure) that can lead to the victim’s death. In this review, we comprehensively describe C. d. ruruima biology and the challenges this subspecies poses for human health, including morphology, distribution, epidemiology, venom cocktail, clinical envenoming, and the current and future specific treatment of envenomings by this snake. Moreover, this review presents maps of the distribution of the snake subspecies and evidence that this species is responsible for some of the most severe envenomings in the country and causes the highest lethality rates. Finally, we also discuss the efficacy of the Brazilian horse-derived antivenoms to treat C. d. ruruima envenomings in Roraima state.